Islamic Religious Education in Forming a Generation with Character and Noble Character - Arif Muzayin Shofwan; Achmad Yusuf; Mujiburrohman; Pahmi Pahmi (Al-Ilmu, 2025)
The character crisis affecting the younger generation demands a strategic role for religious education in shaping individuals with noble character. Islamic Religious Education (PAI) holds significant potential in instilling the moral, spiritual, and social values necessary to shape a generation of integrity. This study aims to analyze the role of PAI in shaping students' character and identify supporting and inhibiting factors within the context of formal education. The method used was a qualitative approach with a case study design in three secondary schools in West Java. Data collection techniques included in-depth interviews, participant observation, and documentation studies. The results indicate that PAI is capable of shaping students' character through the integration of values into learning, teacher role models, and Islamic school culture. Supporting factors include teacher quality, religious habituation programs, and parental involvement, while obstacles include limited learning duration and the influence of digital media. The study's conclusion emphasizes that PAI must be implemented holistically and collaboratively to create a generation that is not only intellectually intelligent but also morally and spiritually strong.